A history of old Norse poetry and poetics - Ross, Margaret Clunies 1942- (Brewer, 2005)
"Guide to and description of the medieval poetic tradition in Scandinavia"--Provided by publisher.
"Guide to and description of the medieval poetic tradition in Scandinavia"--Provided by publisher.
Includes bibliographical references and index
Keywords: Geschichte; Dichtkunst; Literatuurtheorie; Oudnoords; Old Norse poetry -- History and criticism; Poetics -- History; Poetik; Altnordisch; Versdichtung; Literatur